Go East, Old Man: The Ritual Spaces of SS Veterans’ Memory Work - Werther, Steffen; Hurd, Madeleine (Culture Unbound, 2014)
This article uses social-movement analysis to understand the rituals, memory-work and spatialties of Waffen-SS veterans and their sympathizers. Most social-movement analysis focuses on left-wing protesters; our concern is with the marginalized counter-narratives, rituals and -spaces produced by the self-proclaimed misunderstood “heroes” of World War Two. This counter-hegemonic self-definition is essential to these former world-war soldiers who, despite an internal mythology of idealistic self-sacrifice, are vilified in West-European master narra-tives. We discuss how, during the 1990s, veterans and their sympathizers sought to replace rituals of memory-work in the newly-opened East. We look at how the Waffen-SS’s ritual memory-work is “replaced” in alternative settings, including – perhaps surprisingly – Russia itself. Here, Waffen-SS veterans use new, official, semi-sacred places to anchor both an alternative identity and an alternative definition of the central meanings of modern European history.